(3af EOGQI GdENJdGa Odjd GdeaGhV GdaYGds - (3LhOjJ Cj(B, (3ajTQs; (3YdG CMeO(B, s ((3GdbGgQI(B:s (3eQcR GdNHQGJ GdegfjI ddEOGQI(B,s, 1997)
(3eGgh GdJaGhV aj GWGQ af EOGQI GdENJdGa?(B- (3YfGUQ GdJaGhV ef CLd GdEJaGb(B- (3YedjI EOGQI GdENJdGa Yf WQjb GdJaGhV(B- (3GdEYOGO ddJaGhV(B-(3ESJNOGe GdegGQGJ GdEJUGdjI aj GdJaGhV(B- (3ESJNOGe CSGdjH GdJaGhV(B- (3JaGhV GdeMJQajfs
Keywords: (3EOGQI GdCYeGds; (3GdSdhc GdEOGQjs; (3GdeaGhVGJs; (3GdfRGYGJs; (3egGQGJ GdGJUGds